State of the heart - Cohen, Lawrence S.; Finley, Stuart; Minick, Richard ([Washington : American Chemical Society, 1981)
Dr. Lawrence Cohen, professor of medicine at Yale, talks about the current research in the field of cardiology. Dr. Richard Minick, professor of pathology at New York Hospital, Cornell Medical Center, discusses his research demonstrating that a herpes virus may be a factor contributing to cardiovascular disease.
Radio reports, presented by the American Chemical Society.
Durations: 15 min. each.
Issued also as transcripts no. 1,000 and 997.
Keywords: Cardiology -- Research; Heart -- Diseases; Herpesviruses